National Telehealth Service Provider industrial systems design - Danseco, Joselito E. Jr; De Leon, Diwata D.; Sta. Maria, Kevin Michael A.; Suarez, Olivia Graciela V.
The National Telehealth Service Provider (NTSP) is a non-profit organization pioneering in the telemedicine industry in the Philippines. Being the pioneer in its industry, NTSP is expanding its system to meet the increasing demand of its market. In this study, four expansion plans are prepared to help the management design their system: a software plan, labor plan, facilities plan and a service design blueprint. The software plan includes the list of software features for the inclusion in the development of triage, a telemedicine software being develop by the organization. Documentation of the current processes to be supported by Triage, benchmarks with the similar industries such as call center operations and incident ticketing operations, and failure mode analysis was conducted. These data were used to create a program that automatically prioritizes the software features based on the user-inputted budget, developer salary, and cost allowance. The labor plan is a description of the job positions of employees needed by the organization for its expansion and their responsibilities. Documentation of the tasks performed by the employees for NTSP and benchmarking with the call center industry was conducted for this. A zero-based budget labor plan was drafted excluding the number of nurses and domain experts which are both demand-dependent. A table specifying the number of nurses needed for different levels of demand was created. The number of domain experts was not identified since this study recommends a different work configuration for the domain experts by housing them inside NTSP's facility. The facilities plan identifies the location of NTSP's office and its layout. Since the labor plan is a function of demand, the facilities plan created in this study is a function of the number of the employees to be housed. For each number of employees to be housed by the organization, a location and layout plan was recommended. The service design blueprint describes the technology, equipment and manpower needed to reach the doctorless areas. Because doctorless areas may have different reasons for being doctorless and the strategy to reach them will depend on these reasons, an alternative table was created along with their costs and the reason for being doctorless that they address. It is recommended that NTSP conduct further study to properly characterize the doctorless areas so they can select from the table of alternatives constructed in this study. In addition, since NTSP is on the process of expanding, reaching out to more customers and hiring new people, an operations manual was also created to improve the documentation, streamline their processes and ensure that every member of the organization follows procedures.